Risk Factors for Recurrent Anterior Glenohumeral Instability Following a Primary Latarjet Procedure: A Prospective Analysis of 358 Patients. Issue 7 (31st July 2020) - Provencher, Matthew; Peebles, Liam; de Gasperis, Nicola; Golijanin, Petar; Scarso, Paolo; Arner, Justin; DiGiacomo, Giovanni
Objectives: The purpose of this study was to identify historical and demographic risk factors influencing failure rates and inferior clinical outcomes in patients reporting recurrent anterior glenohumeral instability following a primary Latarjet procedure. It was hypothesized that patients who have a greater risk of recurrent instability and worse clinical outcomes following a primary Latarjet procedure can be preoperatively identified on the basis of clinical, demographic, and radiological criteria. Methods: Between 2004 and 2014, patients who were treated with a primary Latarjet by the senior author (GDG) for unidirectional anterior shoulder instability were reviewed. Further inclusion criteria were ≥ 2 traumatic or atraumatic anterior instability events and physical examination and imaging findings consistent with anterior instability. Patients were excluded if they underwent previous ipsilateral shoulder surgery, had a rotator cuff tear, or had voluntary and/or multidirectional instability. Gender, age at first dislocation, duration of instability symptoms, number of dislocation events, age at surgery, bilateral instability, mechanism of dislocation, and quantification of glenoid and humeral head bone loss were recorded. Western Ontario Score Index (WOSI) and Single Assessment Numeric Evaluation (SANE) outcomes scores were collected at minimum five-year follow-up, along with clinical outcomes parameters including evidence of recurrent instability. Results: 358 consecutive patients (372 shoulders) with a mean age of 29.2 years (range = 16 to 68 years) met inclusion criteria at a mean follow-up of 75 months (range = 61 to 89 months). There were 299 men (83.5%) and 59 women (16.5%), of which 86 had bilateral dislocations (24%). Bilateral Latarjet procedures were performed on 14 patients (4.1%). There was a total of 173 patients (48.3%) with an on-track lesion and glenoid bone loss ≤ 13.5%, 154 patients (43%) with on-track lesion but glenoid bone loss >13.5%, and 31 patients (8.7%) with off-track lesions. 17 patients (4.9%) experienced an instability episode following treatment with primary Latarjet. The mean WOSI was 818.2 ± 156.9 for recurrent instability patients while it was 296.4 ± 207.3 for patients with no postoperative instability (F1, 356 = 104.6, p < 0.05). SANE scores were also lower in cases of recurrence (65.9 ± 9.0) when compared to patients that did not report postoperative recurrence (85.8 ± 8.1) (F1, 356 = 98.4 p < 0.05). The mean WOSI score of bilateral instability subjects (438.6 ± 205.8) was higher than those with unilateral instability (256.3 ± 189.6) (F2, 339 = 427.0; p < 0.05), while SANE was similarly worse for bilateral subjects (79.7 ± 8.4) compared to unilateral subjects (87.6 ± 7.1) (F2, 339=23168.9; p < 0.05). The patients with atraumatic dislocations reported WOSI scores that were, on average, higher than those reported for patients with traumatic ones (396.3 ± 216.3 versus 270.6 ± 197.2, respectively; F2, 339 = 380.7; p < 0.05) and mean SANE scores that were lower than the others (81.7 ± 9.4 versus 86.9 ± 7.3, respectively; F2, 339 = 20, 722.3; p < 0.05). The mean postoperative WOSI for female patients in this cohort was higher than that of males (397.3±227.9 and 276.5±197.4 respectively; F2, 339 = 372.9; p < 0.05), while SANE was lower (82.6 ± 8.4 for females and 86.5±7.8 for males; F2, 339 = 19959.6; p < 0.05). The mean postoperative WOSI for subjects who were between 31 and 40 years old at the first instability episode was higher (366.5 ± 236.6) than who were less than 30 years old (F4, 337 = 181.1; p < 0.05). There was no significant difference across age groups with respect to postoperative SANE scores. The mean WOSI score for patients over 40 years old at the time of the surgery was higher (347.2 ± 269.0) than for those under 22 years old (233.3 ± 217.7) and those between 23 and 30 years old (272.0 ± 182.5; (F4, 337 = 181.9; p < 0.05)). SANE scores were not significantly different with respect to patient age at the time of treatment. There was found to be no correlation between the pattern of bone loss (OFF-track, ON-track < 13.5%, ON -track > 13.5%) recurrent instability and clinical outcomes. Conclusion: 4.9% of patients treated with primary Latarjet experienced recurrent anterior instability postoperatively. Preoperative risk factors included history of bilateral shoulder instability and atraumatic mechanism of dislocation. Poorer postoperative outcome scores independent of recurrent instability included age > 31 years, female gender, having more than seven instability events prior to surgery, bilateral instability, and atraumatic mechanism of first-time dislocation. This is the first clinical study to provide evidence behind specific demographic and historical factors that predispose patients to a greater risk of recurrent instability and inferior clinical outcomes following a Latarjet. This has implications on both clinical treatment and patient education to more accurately evaluate Latarjet candidates.